How Big Is the Random Walk in GNP? - Cochrane, John H. (Journal of Political Economy, 1988)
This paper presents a measure of the persistence of fluctuations in GNP based on the variance of its long differences. That measure finds little long-term persistence in GNP. Previous research on this question found a great deal of persistence in GNP, suggesting models such as a random walk. A reconciliation of this paper's results with previous research shows that conventional criteria for time-series model building can produce misleading estimates of persistence.